InGaP grown on Ge (100) by molecular beam epitaxy: a spectroscopic ellipsometry study - D’Costa, Vijay Richard (2016)
We investigated the optical properties of disordered In0.52Ga0.48P alloys by spectroscopic ellipsometry in the far-infrared to ultraviolet energy range (0.037–5.1 eV). The alloys were grown on Ge (100) substrate by solid-source molecular beam epitaxy. The far-infrared dielectric function reveals two absorption peaks that can be attributed to InP- and GaP-like vibrational modes. The visible-UV dielectric function of In0.52Ga0.48P alloys nearly lattice-matched to Ge shows the critical points E 0, E 1, and E 2, energies of which are determined using a derivative analysis. A weak transition that can be identified as the E 1 + Δ1 critical point is revealed. The vibrational frequencies and the transition energies in In0.52Ga0.48P are lower relative to In0.49Ga0.51P lattice-matched to GaAs. The downward shifts in E 0 and phonons can be estimated using the compositional dependence of E 0 and phonons of bulk alloys.